Sustainable Land Management (SLM) Practices in Drylands: How Do They Address Desertification Threats? - Zachariah, Samuel; Mpundu, Mubanga (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Desertification poses a significant and growing threat to drylands worldwide, profoundly impacting biodiversity, livelihoods, and food security. These regions, covering approximately 41% of the Earth's land surface and inhabited by over 2 billion people (United Nations, 2019), are particularly vulnerable due to their low precipitation and fragile ecosystems. Desertification, driven by climatic variations and human activities, leads to the degradation of land, diminishing agricultural productivity, deteriorating water quality, and exacerbating poverty (D'Odorico et al., 2013). In response to these challenges, Sustainable Land Management (SLM) practices have emerged as critical tools in combating desertification and restoring ecological balance in drylands. SLM encompasses a diverse array of strategies aimed at sustainably managing land resources to enhance soil fertility, conserve water, and support resilient agricultural and pastoral systems. These practices not only mitigate the adverse effects of desertification but also contribute to the sustainable development goals by improving ecosystem health and supporting local livelihoods. This paper explores the various SLM practices implemented in drylands, evaluating their effectiveness in mitigating desertification threats through a synthesis of case studies and scientific evidence. By highlighting successful strategies and identifying challenges in the adoption and implementation of SLM practices, this study aims to provide insights into enhancing sustainable land management strategies in the face of escalating desertification pressures.